Employer Sponsored Retirement Savings Plans - Rachel Dorman; Lisa M. Leslie; Michael S. Gutter; Martie Gillen; Josephine Turner (EDIS)
A financially secure retirement is a goal for many workers, and the ability to achieve that plan can be helped by employer-sponsored retirement plans. Learn more in this 3-page fact sheet written by Rachel Dorman, Lisa M. Leslie, Michael S. Gutter, Martie Gillen, and Josephine Turner, and published by the UF Department of Family Youth and Community Sciences, April 2012.